Engaging youth at risk of violence in services: Messages from research. (January 2023) - Axford, Nick; Tredinnick-Rowe, John; Rybcyznska-Bunt, Sarah; Burns, Lorna; Green, Finlay; Thompson, Tom
Highlights: Services are more likely to attract and retain youth if they are co-designed. Services are likely to be more engaging for youth if they are personalised. Practitioners working with youth need to be caring, open, attentive and genuine. The service system needs to make it easy for youth to engage with services they need. Parents/carers and peers can support young people's engagement in services. Abstract: Addressing youth violence is a public health priority given its prevalence, harms and costs to society. Services designed to prevent or reduce youth violence exist. However, their effectiveness depends on youth engaging with them. To our knowledge, there is no overview of the evidence on how to support this process. This article therefore aims to identify key messages from the scientific literature about how services can best engage youth at risk of involvement in violence. We undertook a rapid review of the evidence on youth engagement in services, prioritising English language studies published from 2010- which included youth aged 10–14 years and were conducted in high-income countries. Key messages for practice relate to 12 themes: co-designing services with youth; personalising provision to youth needs and preferences; recruiting staff with suitable experience and qualities; developing positive practitioner-participant relationships; nurturing an enabling service system; creating an inviting service environment; designing interesting activities and service content; encouraging peer engagement; securing parent/carer support; exploring opportunities for service integration; proactively including marginalised groups; and exploiting digital opportunities. While we could identify key messages from the literature, more prospective empirical research is needed to test the effectiveness of strategies in isolation and combination. This includes exploring what works for whom and in what circumstances.